EFFECTS OF EMOTIONAL REGULATION PSYCHOEDUCATION ON ADOLESCENT SELF-CONTROL IN VOCATIONAL EDUCATION HIGH SCHOOLS - Avelina, Yuldensia; Riswanti Herminsih, Adelheid; Lambertina Barek Aran, Maria; Andika Putri, Agustina (Jurnal Keperawatan Sriwijaya, 2026)
Aim: This study aimed analyzing the differences in self-control levels before and after providing emotional regulation psychoeducation to vocational education high schools. Method: The study used a quasi-experimental one-group pre-test post-test design. The sample consisted of 32 students selected using purposive sampling. The instruments used were the self-control questionnaire from Arfian (2021) and the Work Unit for emotional regulation psychoeducation. Data analysis used the McNemar test to analyze the influence of both variables. Result: The results showed that before receiving emotional regulation psychoeducation, 23 (71.9%) adolescents had poor self-control and 9 (28.1%) had good self-control. After receiving emotional regulation psychoeducation, 30 (93.8%) adolescents had good self-control and 2 (6.3%) had poor self-control. The results of the bivariate analysis using the McNemar test showed a p-value (0.000) <α (0.05). Thus, there is a significant effect of emotional regulation psychoeducation on self-control in vocational high schools. Conclusion: There was a significant effect of emotional regulation psychoeducation on adolescents’ self-kontrol in vocational high schools. Students were expected to recognize their emotions and exercise self-kontrol over emerging negative emotions using the self-kontrol techniques that had been taught, including deep breathing relaxation and positive affirmations.